Islet Inflammation and Metabolic Homeostasis - Collier, Jason; Burke, Susan (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book provides a resource for the science or medical professional interested in islet biology. With a mix of review articles and studies showing primary data, new advances in islet inflammation and metabolic homeostasis are highlighted. The topics are succinctly presented by distinct viewpoints. An introduction to the Special Issue, with summaries of the studies included, is provided by the Guest Editors.